Thermal Expansion of Triaxially Stressed Mudstone at Elevated Temperatures up to 400°C - Zi-jun Feng; Meng-meng Qiao; Fu-ke Dong; Dong Yang; Peng Zhao (Advances in Materials Science and Engineering)
In order to study the thermal deformation of the rock that surrounds underground engineering projects with elevated temperatures (e.g., underground coal gasification, coal in situ pyrolysis, in situ oil and gas extraction from oil shale, geothermal energy extraction from rock, among others), a servocontrolled machine (model IMT-HTP 100F) was used to examine the thermal expansion of triaxially stressed mudstone at temperature up to 400°C. Two distinct stages of thermal expansion were found at temperatures up to 400°C: very small thermal expansion below 50°C, followed by almost constant thermal expansion at 50–400°C. This linear thermal expansion coefficient of triaxially stressed mudstone did not increase in the range 50–400°C. The effect of the applied triaxial stress was on both close cracks and impeded grain expansion and the swelling of the rock. Mudstone had a larger linear thermal expansion coefficient than either sandstone or limestone, in that order. The potential energy theory was used to explain the intrinsic variation of thermal expansion of the different rock types.